National-culture image of the japanese phraseology (Journal of Oriental Studies, 2016)
this article about national – cultural image Japanese phraseology. the fact that different national character of Japanese phraseology from other languages. it also that nature directly affects the phraseology.
Keywords: Phraseology; image; means; translation